PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA PT BANK RAKYAT INDONESIA TBK PERIODE 2012-2023 - Meylani, Adelia; Prasetyo, Hendri (Journal of Research and Publication Innovation, 2024)
This study aims to test the influence of the variables Capital Adequacy Ratio (CAR) and Operational Costs of Operational Income (BOPO) on Return on Asset (ROA) in PT Bank Rakyat Indonesia Tbk period 2012-2023. The analytical techniques used are Double Linear Regression, Classical Assumption Test, T Test, F Test and Determination Coefficient Test, processed using the help of SPSS 26. Hypothesis Tests use t Test to test partial relationships and f Tests to test influences together. The results of data analysis showed that the variable Capital Adequacy Ratio (CAR) and Operational Costs of Operational Income (BOPO) simultaneously influenced the return on assets (ROA) given the calculated result > ftable is 5,17 > 4,25 and the significance value was 0,03 < 0,05. Partially, the capital adequacy ratio (Car) variable has no influence and no significance on the return of operational income (ROA) with the thitung result < ttable is 0,612 < 2,228 with a significant value of 0,55 > 0,05 and the operational cost variable Operational Revenue (BOPO) has a negative and significant influence on the Return on Asset (RO A) with a thung result > t table is -2,576 > 2,228, with a signifying value of 0.03 < 0.05.